Complete rupture of unscarred uterus with delayed symptoms: Case report and possible mechanism. Issue 8 (3rd May 2020) - Nishikawa, Shigeki; Shibata, Takashi; Kato, Hiroki; Kotsuji, Fumikazu; Nakago, Satoshi
Abstract: Uterine ruptures typically occur suddenly, have obvious symptoms, and may require urgent treatment. We experienced a case of complete rupture of an unscarred uterus that was undetected for 9 days. We report the clinical course and possible factors that led to it. Nine days after delivery, complete rupture of the posterior uterine wall was diagnosed by magnetic resonance imaging. The colon and ovaries were tightly adhered to the posterior uterine body. When this adhesive lesion was detached, 7 cm horizontal defects of the muscular layer were revealed. The ruptured wound was repaired. Magnetic resonance imaging 1 year postoperatively showed no thinning of the repaired lesion and suggested successful reperfusion. Mild clinical course despite complete uterine rupture was presumably because of adhesion of the ovaries and intestines to the rupture site.